2021
DOI: 10.1007/s00701-021-04728-z
|View full text |Cite
|
Sign up to set email alerts
|

Respond of the different human cranial bones to pin-type head fixation device

Abstract: Background At this juncture, there is no consensus in the literature for the use and the safety of pin-type head holders in cranial procedures. Methods The present analysis of the bone response to the fixation of the instrument provides data to understand its impact on the entire skull as well as associated complications. An experimental study was conducted on fresh-frozen human specimens to analyze the puncture hole due to the fixation of each single pin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Interestingly, for the 36°/36° pin configuration plus the 40° rocker isolated, we found the deepest penetrations on the single-pin side for the middle fossa approach. This finding is congruous with the results of Visentin et al 9 . With the middle fossa approach, the single-pin hits the frontal bone basally near the air-filled sinuses, where bone density is also rather low.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, for the 36°/36° pin configuration plus the 40° rocker isolated, we found the deepest penetrations on the single-pin side for the middle fossa approach. This finding is congruous with the results of Visentin et al 9 . With the middle fossa approach, the single-pin hits the frontal bone basally near the air-filled sinuses, where bone density is also rather low.…”
Section: Discussionsupporting
confidence: 89%
“…A previous cadaveric study by Visentin et al analyzed cranial pin penetration depths of two commercially available pin-cone angles (35°: commercial adult pin; 43°: commercial pediatric pin) by means of cone beam CT images, assessing the single-pin side 9 . The group confirmed that the smaller pin-cone angle did result in deeper bone penetrations, and that bone penetration depth generally increased with the applied pin force (180 N to 270 N).…”
Section: Introductionmentioning
confidence: 99%
“…Hiwatari et al 3 recommend that when using this fixation system in surgical procedures, the site of pin application, skull thickness, and fragility should be rigorously observed, along with appropriate control of compressive forces exerted by the head structure. Visentin et al [46] reached a conclusion in their study regarding the recommendation for head support use, which depends on the patient's history and cranial thickness to reduce complications associated with pin-type head support during clinical application.…”
Section: Cranial Fracture and Depressionmentioning
confidence: 99%